BINARY DATA TRANSMISSION ON CHAOTICALLY FORMED CARRIER FREQUENCIES - Maksim S. Grebenev; Alexander V. Kondrashov; Vadim V. Perepelovsky (Известия высших учебных заведений России: Радиоэлектроника, 2018)
In this paper, the method of binary data transmission and receiving is first suggested and experimentally investigated. The method uses dynamical chaos as a source of multiple carrier frequencies. On the server side, the transmitter configures informational signal in the form of frequency grid with chaotically varying frequencies of the spectrum with their amplitudes corresponding to transmitted information message. On the client side, the transmitted information is re-stored using chaotically selected spectral windows. Synchronization of the server and client dynamic chaos generators is achieved by means of TCP/IP protocol. Suggested method is based on combined transmission of information message via transmission channel and background signal. Power of background signal significantly exceeds power of informational one. The method allows using different informational signal as a background signal, such as voice message. The addition of low power chaotically formed frequency grid signal does not lead to significant background signal formation either in spectral or in time domain. Thus, the described method allows repeated application of the transmission channel. The effect of signal-to noise ratio of the order of the filter implementing the spectral windows in the receiver and the width of the spectral window is investigated. Signal-to-noise ratio can be reduced with increasing filter order and spectral window width.